The expression of CD11/CD18 molecules on rabbit leucocytes: identification of monoclonal antibodies to CD18 and their effect on cellular adhesion processes. - Galea-Lauri, J; Blackford, J; Wilkinson, J (1993)
The monoclonal antibodies, L13/64 and RCN1/21, raised against rabbit leucocytes, have been shown, by sequential immunoprecipitation and immunoblotting, to react with the rabbit CD18 molecule. They recognise not only surface-expressed CD18 but also an intracellular form which appears to be partially glycosylated. The expression of the CD11 and CD18 glycoproteins on a wide variety of rabbit leucocyte populations has been investigated by flow cytometry, using these two monoclonal antibodies (Mabs), together with others which recognise human CD11 and CD18 proteins but cross-react with rabbit tissues. The distribution of these leucocyte integrin molecules has been shown to be similar to that observed in humans and determination of the N-terminal sequence of rabbit CD11b shows strong homology with human and mouse sequences. Of four anti-rabbit CD18 Mabs tested, only one, L13/64, has been shown to be capable of inhibiting the adhesion of fMLP-stimulated neutrophils to gelatin coated plastic and the homotypic aggregation of PMA-stimulated T cells, both of which assays have been shown to be CD18-dependent. RCN1/21 causes aggregation of unstimulated neutrophils, but it is not known whether this is due to cellular activation or agglutination.